STT]DENT'S ACHIEVEMENT ON BIOLOGY OF THE STUDENT OF ACCELERATION CLASS OF SMA NEGERI III SURAKARTA, EMPHASIZED ON THEIR LEARNING METHOD, LEARNING MOTIVATION AND THEIR EMOTTONAL QUOTIENT (EQ - HAMIDAH, LILIK NUR; SAJIDAN, SAJIDAN; SUMANTO, SUMANTO (Prodi Pendidikan Biologi FKIP UNS, 2006)
AbstractThis is the descriptive-quantitative research which aimed to know the student achievement on biologywhich specify in a view point of their learning method, motivation and EQ. Acceleration class program of2d grade student of SMA Negeri III Surakarta was the object of this research. Clustered random salmplingwas used to collect the data, which was held by questionaire and documentation. Analysis of Variance wasused to analyze the data.The result showed that any learning method was suitable for the student of acceleration pragrams,since we know that they have the more prominent academic ability. Various EQ and learning motivationwere occur, then can be concluded that EQ and learning motivation were still affected their achievement.Key words : Acceleration class programs, Student achievement